Effect of the Adoption of a Comprehensive Electronic Health Record on Graduate Medical Education: Perceptions of Faculty and Trainees. Issue 8 (August 2018) - Rosdahl, Jullia A.; Rudd, Mariah; Benjamin, Robert; Wiener, John S.; Sloane, Richard; Brown, Audrey; Robert Lee, W.; Turner, David; Qin, Rosie; Atwater, Amber Reck
Abstract : Objectives: Health systems are adopting electronic health records (EHRs). There are few studies on the effects of EHR implementation on graduate medical education. The authors sought to longitudinally assess perceptions of the impact of EHRs on graduate medical education during implementation and 2 years after implementation. Methods: A survey was distributed to faculty and trainees during the first year (2013) of adoption of the EHR system. A follow-up survey was distributed 2 years later (2015). The χ 2 test was used to compare the quantitative responses, and factor analysis was conducted to identify correlations between items. Free text responses were analyzed qualitatively. Results: The initial survey (in 2013) included 290 faculty and 106 trainees; the follow-up survey (in 2015) included 353 faculty and 226 trainees. In 2013, respondents had a positive impression of EHRs. During the implementation phase, participants believed that face-to-face teaching was negatively affected ( P = 0.001). Faculty believed EHRs had a negative effect on trainees' ability to take a history/conduct physical examinations ( P = 0.002) and to formulate a differential diagnosis/plan independently ( P = 0.003). In 2015, faculty opinions of the impact of the EHR remained unchanged; trainee responses were more positive than in 2013 in some areas. Qualitative analysis showed that the most frequent strategies to enhance the educational process were the development of EHR skills and improved chart access and note assistance. Conclusions: Respondents remain positive about the EHR 2 years after implementation. Faculty remain concerned about its effect on the educational process, whereas residents appear more positive regarding the potential for EHRs to enhance their education. Abstract : Health systems are adopting electronic health records (EHRs), and few studies have demonstrated the effects of EHR implementation on graduate medical education. Using a two-part survey, faculty and trainees were queried about the impact of the EHR during their adoption phase and 2 years later. Results demonstrated that faculty opinions of the impact of the EHR remained steadily positive throughout implementation and 2 years later, whereas trainee opinions improved. Faculty expressed concern about its effect on the educational process, and residents appeared more positive regarding the potential for EHR to enhance their education.Supplemental digital content is available in the text.